Exploring the Determinants of Consumer Repurchase Intention in Omnichannel Retailing: Evidence from AZKO Indonesia - Muh Yusuf Maulana; Ananda Sabil Husein; Nur Prima Waluyowati (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – “This study aims to examine the effect of channel integration on consumers’ repurchase intention in AZKO Indonesia by considering perceived assortment and perceived value as mediating mechanisms within an omnichannel retailing context. Design/methodology/approach – This study employed a quantitative explanatory design. 200 AZKO Indonesia customers who had both in-person and online buying experiences provided the data. Purposive sampling was used to collect the data, which were then subjected to partial least squares structural equation modelling (PLS-SEM) using SmartPLS 3.0. Finding/Results – Channel integration significantly enhances repurchase intention, both directly and indirectly through perceived assortment and perceived value. These results confirm the role of consumer perceptions as key mechanisms linking omnichannel integration to repurchase intention.” Originality/Value – Provide This study contributes to omnichannel retailing literature by explaining repurchase intention through the integration of Service-Dominant Logic and the Theory of Consumption Values. Its novelty lies in examining perceived assortment and perceived value as parallel mediators in the context of AZKO Indonesia’s omnichannel retailing.